An analytical study of some special variables associated with the stages of the overwhelming hit in volleyball - JADDOA KADHIM AL-NUAIMI, SAWSAN (International Journal of Psychosocial Rehabilitation, 2020)
The world is witnessing at the present time great progress in the application of modern scientific foundations in the field of sports, which has greatly influenced the level of performance and achievement in all activities and sports, including the game of volleyball with its offensive and defensive skills, and the overwhelming skill is one of the offensive skills that the team can score directly or indirectly through it, so you need an evaluation based on modern scientific foundations based on the results of the kinematic analysis.